Local Service Delivery of Potable Water in the Philippines: National Review and Case Analysis - Danilo C. Israel (Philippine Institute for Development Studies (PIDS), 2009)
This study reviewed the local service delivery of potable water nationally and analyzed the same in the case study areas of Dumaguete City and Agusan del Sur. Data and information for the national review were generated from the relevant literature while those for the case analysis were through a survey done in late 2008 and early 2009. The national review found that although pertinent laws, institutions, strategies, and programs on potable water service delivery were already in place, institutional problems remained. It further asserted that while the country may be heading toward meeting its national and MDG objectives related to the provision of potable water, more needs to be done with the limited time at hand. Among the important conclusions of the case study was that Dumaguete City has met or is about to meet national and MDG objectives related to potable water delivery while Agusan del Sur and at least some of its municipalities still have to work harder to meet them. The study further found that the price, quality, and accessibility of potable water were major factors influencing households in their choice of water source. Furthermore, it asserted that there were key issues and challenges facing local water service delivery most of which were institutional in nature. Based on the results, findings, and conclusions of the national review and case analysis, the study suggested some recommendations intended for the further development of local service delivery of potable water nationally, in the case study sites and in other local areas.
Keywords: 330; millennium development goals (MDG); potable water; local service delivery; water district; water service providers; Wasserversorgung; UN-Entwicklungsziele; Ländlicher Raum; Philippinen